Alteration of Forebrain Neurogenesis after Cervical Spinal Cord Injury in the Adult Rat - FELIX, Marie-Solenne; Popa, Natalia; DJELLOUL, Mehdi; Boucraut, José; Gauthier, Patrick; Bauer, Sylvian; Matarazzo, Valery A. (Frontiers in Neuroscience, 2012)
Spinal cord injury (SCI) triggers a complex cellular response at the injury site, leading to the formation of a dense scar tissue. Despite this local tissue remodeling, the consequences of SCI at the cellular level in distant rostral sites (i.e. brain), remain unknown. In this study, we asked whether cervical SCI could alter cell dynamics in neurogenic areas of the adult rat forebrain. To this aim, we quantified BrdU incorporation and determined the phenotypes of newly generated cells (neurons, astrocytes, or microglia) during the subchronic and chronic phases of injury. We find that subchronic SCI leads to a reduction of BrdU incorporation and neurogenesis in the olfactory bulb and in the hippocampal dentate gyrus. By contrast, subchronic SCI triggers an increased BrdU incorporation in the dorsal vagal complex of the hindbrain, where most of the newly generated cells are identified as microglia. In chronic condition 90 days after SCI, BrdU incorporation returns to control levels in all regions examined, except in the hippocampus, where SCI produces a long-term reduction of neurogenesis, indicating that this structure is particularly sensitive to SCI. Finally, we observe that SCI triggers an acute inflammatory response in all brain regions examined, as well as a hippocampal-specific decline in BDNF levels, which could explain the SCI-mediated distant effects on forebrain neurogenesis. This study provides the first demonstration that forebrain neurogenesis is vulnerable to a distal SCI.